Effects of sequential treatment with intermittent parathyroid hormone and zoledronic acid on particle‐induced implant loosening: Evidence from a rat model. Issue 7 (17th April 2019) - Hu, Bin; Wu, Haobo; Shi, Zhongli; Ying, Zhimin; Zhao, Xiang; Lin, Tiao; Hong, Jianqiao; Wang, Yangxin; Yang, Yute; Cai, Xunzi; Yan, Shigui
ABSTRACT: Particle‐induced implant loosening is a major challenge to long‐term survival of joint prostheses. Administration of intermittent parathyroid hormone (PTH) has shown potential in the treatment of cases of early‐stage periprosthetic osteolysis, while sequential administration of intermittent PTH (iPTH) and bisphosphonates (Bps) has achieved significant effects on treatment of postmenopausal osteoporosis. The objective of this study was to determine whether sequential treatment could preserve bone mass and implant fixation during a pathological course of peri‐implant osteolysis in a rat model. Ninety male Sprague Dawley rats were randomly divided into nine groups, four of which were used for confirmation of establishment of the peri‐implant osteolysis model at two time points, while the other five were used to determine the efficiency of the sequential treatment on peri‐implant osteolysis. Implant fixation and peri‐implant bone mass were evaluated using biomechanical testing, micro‐CT analysis, and histology at 6 and 12 weeks postoperative. The biomechanical test demonstrated that the maximum loading force during a push‐out test was significantly elevated in the sequential treatment group compared to the osteolysis group and iPTH withdrawal group at 12 weeks. Peri‐implant bone morphology also indicated a robust increase in bone volume in the sequential treatment group. Sequential administration of iPTH and Bps was effective in preventing experimental peri‐implant osteolysis, resulting in improved implant fixation and increased peri‐implant bone volume. Clinical significance: The innovative application of sequential treatment in peri‐implant osteolysis could be used clinically to improve the prognosis of patients with early‐stage periprosthetic osteolysis. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:1489–1497, 2019.